Vacancy defect control of colossal thermopower in FeSb2 - Qianheng Du (Nature Portfolio, 2021)
Abstract Iron diantimonide is a material with the highest known thermoelectric power. By combining scanning transmission electron microscopic study with electronic transport neutron, X-ray scattering, and first principle calculation, we identify atomic defects that control colossal thermopower magnitude and nanoprecipitate clusters with Sb vacancy ordering, which induce additional phonon scattering and substantially reduce thermal conductivity. Defects are found to cause rather weak but important monoclinic distortion of the unit cell P n n m → P m. The absence of Sb along [010] for high defect concentration forms conducting path due to Fe d orbital overlap. The connection between atomic defect anisotropy and colossal thermopower in FeSb2 paves the way for the understanding and tailoring of giant thermopower in related materials.